PERAN SEKOLAH SEBAGAI AGEN SOSIALISASI DALAM PENANAMAN NILAI SOSIAL DAN PEMBENTUKAN KARAKTER PESERTA DIDIK: Perspektif Sosiologi Pendidikan - Zalfaa zayyana; Nur Khasanah; Kerwanto Kerwanto; Akhmad Kharis Kurniawan (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
The weakening of social values and the increasing occurrence of various forms of deviant behavior among students indicate the urgent need to strengthen character education within the educational system. Although studies on character education have developed extensively, discussions that position schools as agents of socialization within the perspective of the sociology of education remain relatively limited. This article aims to analyze the role of schools as agents of socialization in instilling social values and shaping students’ character. This study employs a qualitative approach using a literature review method by analyzing various relevant scholarly sources. The findings reveal that schools function as social institutions that transmit values, norms, and social ethics through the curriculum, school culture, social interactions, and the role modeling of educators. The socialization process plays an important role in shaping students’ character, particularly in fostering social awareness, responsibility, and the ability to adapt within society. The novelty of this study lies in its analysis of the function of schools as spaces for value socialization that systematically shape students’ character through social dynamics within the educational environment. These findings affirm that character education should be understood not only as a pedagogical process but also as a social process embedded within the structure and culture of schools.